Security Challenges: Analyzing Violence from a Multidisciplinary Research Perspective - Enita Čustović (Društvene i Humanističke Studije)
This paper examines violence as a form of deviant behavior through a multidisciplinary lens, reflecting social, economic, and cultural tensions in contemporary societies. The text provides an introduction to the thematic issue on violence and, through a review of the content and research findings of the articles published in this section, examines violence in various forms, including physical, emotional, psychological, and structural, as well as the growing presence of cyber violence in the digital age. The authors emphasize the role of media in normalizing violence, particularly among youth, and argue for the need for holistic, interdisciplinary responses involving education, social programs, legal frameworks, and collective efforts to prevent and reduce violence. The study highlights the importance of empathy, solidarity, and resilience within communities, and calls for the rethinking of security from a humanistic perspective. The work concludes that sustainable violence prevention requires the involvement of multiple disciplines and actors, including educational institutions, local communities, and the media.